2014
DOI: 10.1021/es500234y
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Studies of Silver Released from Silver Nanoparticles in Aqueous Media Simulating Sweat, Laundry Detergent Solutions and Surface Water

Abstract: From an increased use of silver nanoparticles (Ag NPs) as an antibacterial in consumer products follows a need to assess the environmental interaction and fate of their possible dispersion and release of silver. This study aims to elucidate an exposure scenario of the Ag NPs potentially released from, for example, impregnated clothing by assessing the release of silver and changes in particle properties in sequential contact with synthetic sweat, laundry detergent solutions, and freshwater, simulating a possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 41 publications
4
53
0
Order By: Relevance
“…Hedberg et al (2014) used a different approach to address the Ag release from textiles in real life scenarios, exposing AgNP impregnated textiles to artificial sweat, laundry detergent and water solution in sequential and separate exposures. Their findings showed that Ag release from sequential exposures was by approximately a factor of 2 lower than the sum of release from separate exposures, which illustrates the importance of choosing an experimental setup to mimic the real world scenarios of textile use (Hedberg et al, 2014).…”
Section: Ac5: Fabrics Textiles and Apparelmentioning
confidence: 99%
“…Hedberg et al (2014) used a different approach to address the Ag release from textiles in real life scenarios, exposing AgNP impregnated textiles to artificial sweat, laundry detergent and water solution in sequential and separate exposures. Their findings showed that Ag release from sequential exposures was by approximately a factor of 2 lower than the sum of release from separate exposures, which illustrates the importance of choosing an experimental setup to mimic the real world scenarios of textile use (Hedberg et al, 2014).…”
Section: Ac5: Fabrics Textiles and Apparelmentioning
confidence: 99%
“…Silver and TiO 2 are among the most commonly encountered nanoparticles applied in consumer products in recent years (www.nanotechproject.org). However, their prevalent usage is of concern because of their possible release to the environment (Al-Kattan et al, 2014;Gondikas et al, 2014;Gottschalk and Nowack, 2011;Hedberg et al, 2014;Kaegi et al, 2013;Lombi et al, 2014), which may result in exposure of the ecosystem components and lead to adverse effects (Ali et al, 2014). Agglomeration and dissolution studies are providing valuable contributions for the speciation of the nanoparticles in the environment which are essential to develop an understanding of the mobility and transformation of ENPs.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Their rapidly growing use inevitably releases large amounts of AgNPs to the environment and may cause environmental problems. 3,4 Despite increasing interest in their environmental effect and biological toxicity of AgNPs over the past several years, 5−8 the mechanisms of AgNPs toxicity remain largely in a state of "discussion" due to the complicated nature of the transformation and toxicology of AgNPs after entering organisms.…”
mentioning
confidence: 99%